Improving Nutrition Facts of Cassava and Soybean Residue Through Solid-State Fermentation by Pleurotus ostreatus Mycelium: A Pathway to Safety Animal Feed Production - Nguyen Thi Bich Hang; Chi Cuong Doan (Fermentation)
The overwhelming amount of cassava residues and okara are a foremost challenge for the food processing industry environmental loading. The purpose of this article is to utilize Pleurotus ostreatus mycelium to ferment solid cassava and soybean residue, resulting in mycelial biomass with nutritional values and promising prebiotic activities from fermented waste sources. By blending a ratio of 80% cassava and 20% soybean residues, the mycelium spread rapidly after 3 days of culture, from 1.73 mm on the first day to 13.32 mm on the third day, and completely covered the surface after 9 days of culture (120 mm). Using the solid-state fermentation (SSF) method allowed us to improve the content of substances isolated from mycelium biomass, where polysaccharide content rose by 2.1 times to 3.44 mg/g, and the protein content increased by 1.84 times over the initial substrate. The prebiotic activity of extracted PS was greatest in P. acidilactici NBD8 (1.58); for L. pentosus NH1, L. argentoraten NH15, and L. plantarum WCFS1 strains, the indices were 0.11, 0.17, and 0.3, respectively. The SSF process with P. ostreatus mycelium has the potential to be an effective method for improving the nutrition and digestibility of soybean and cassava residues for application in the production of nature-derived animal feed, as well as contributing to fully utilized agricultural residue, agriculture’s circular economy, reducing environmental issues, and achieving the net-zero carbon emissions target by 2050, as the Vietnam government committed to achieving during the COP26 World Leaders’ Summit in 2021.